Impact of Using Hermetic Packaging and Preservative on Physical Properties of Rice Bran During Storage - Muhammad Ridla; Maria Rosalia Bengang Sabaleku; Nahwori Nahwori (Buletin Peternakan, 2023)
Rice bran is one of the feed ingredients used in various types of animal rations in Indonesia. In addition to containing anti-nutrients, rice bran has also a low storability. This research was conducted to study the impact of using hermetic packaging and a preservative containing calcium propionate (ProsidTM MI 208) application on the physical properties of rice bran during storage. The factorial completely randomized design (CRD), 3 x 4 with 4 replications was applied. The first factor was storage time 0 (W0), 30 (W30), and 60 (W60) days; the second factor was burlap sack + 0 ppm calcium propionate (P1), burlap sack + 160 ppm calcium propionate (P2), hermetic sack + 0 ppm calcium propionate (P3), and hermetic sack + 160 ppm calcium propionate (P4). The variables measured were moisture content (MC), bulk density (BD), tapped density (TD) dan true density (TDS). The obtained data were analyzed using if there was a significant difference, followed by Duncan's multiple range test. The results showed that storage time significantly (P<0.05) increased the MC and decreased the BD, TD, and TDS values. The increasing MC and the decreasing BD, TD, and TDS values of the rice bran during storage were higher (P<0.05) in the burlap sakcs than in the hermetic sacks packaging both with and without the addition of calcium propionate. The combination of using hermetic sacks with the application of calcium propionate could further increase to maintain of the physical properties of rice bran from the damage. The use of a hermetic sack and the application of calcium propionate could maintain the quality of rice bran and increase the resistance of rice bran to damage during 60 days of storage.